Fluorodopa is a Promising Fluorine‐19 MRI Probe for Evaluating Striatal Dopaminergic Function in a Rat Model of Parkinson's Disease. Issue 7 (28th October 2016) - Yanagisawa, Daijiro; Oda, Keisuke; Inden, Masatoshi; Morikawa, Shigehiro; Inubushi, Toshiro; Taniguchi, Takashi; Hijioka, Masanori; Kitamura, Yoshihisa; Tooyama, Ikuo
Abstract : Parkinson's disease (PD) is a progressive neurodegenerative disorder characterized by the loss of dopaminergic neurons in the substantia nigra projecting to the striatum. It has been estimated that approximately 80% of the striatal dopamine and 50% of nigral dopaminergic neurons are lost before the onset of typical motor symptoms, indicating that early diagnosis of PD using noninvasive imaging is feasible. Fluorine‐19 ( 19 F) magnetic resonance imaging (MRI) represents a highly sensitive, easily available, low‐background, and cost‐effective approach to evaluate dopaminergic function using non‐radioactive fluorine‐containing dopaminergic agents. The aim of this study was to find a potent 19 F MRI probe to evaluate dopaminergic presynaptic function in the striatum. To select candidates for 19 F MRI probes, we investigated the following eight non‐radioactive fluorine‐containing dopaminergic agents: fluorodopa (F‐DOPA), F‐tyrosine, haloperidol, GBR13069 duhydrochloride, GBR12909 duhydrochloride, 3‐bis‐(4‐fluorophenyl) methoxytropane hydrochloride, flupenthixol, and fenfluramine. In 19 F nuclear magnetic resonance measurements, F‐tyrosine and F‐DOPA displayed a relatively higher signal‐to‐noise ratio value in brain homogenates than in others. F‐DOPA, but not F‐tyrosine, induced the rotational behavior in a 6‐hydroxydopamine (6‐OHDA)‐induced hemiparkinsonian rat model. In addition, a significantly high amount of F‐DOPA accumulated in the ipsilateral striatum of hemiparkinsonian rats after the injection. We performed 19 F MRI in PC12 cells and isolated rat brain using a 7T MR scanner. Our findings suggest that F‐DOPA is a promising 19 F MRI probe for evaluating dopaminergic presynaptic function in the striatum of hemiparkinsonian rats. © 2016 Wiley Periodicals, Inc. Abstract : Fluorodopa displayed an intense peak with a high signal‐to‐noise ratio value in brain homogenates. 19 F MRI using a 7T ultra high‐field MR scanner successfully detected 19 F MR signal of fluorodopa in the isolated rat brain. Our findings suggest that fluorodopa is a promising imaging probe for evaluating dopaminergic function.